2013
DOI: 10.1007/978-3-642-40352-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Analysis and Definition for Eco-factories: The Case of EMC2

Abstract: Abstract. Climate change mitigation and the EU2020 strategy foster energy efficiency in Europe's future manufacturing landscape. These challenges make high demands to SMEs as well to MNCs. The paper gives insight to an approach on Eco-factories based on the EU-funded FP7 project EMC2. Ecofactories will enable the quantum leap in integrating environmental issues in brownfield and greenfield factory planning and factory operation. The paper focuses on the identification, structuring and definition of requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The usefulness of Discrete-Event-Simulation (DES) in manufacturing application is nowadays undisputable and has been demonstrated in various studies [3], hence diverse commercial simulators like Arena, FlexSim, Plant-Simulation, Anylogic, just to name a few, support the planning and optimization of manufacturing systems. But the implementation of energy related functions or indicators or other environmental-oriented functions within commercial simulators is not realized yet, although recent empirical studies have shown that companies see the combination of simulation enhanced by the empirical perspective as a supporting methodology [4] and requirements for future eco-oriented factories claim the same issue [5]. Approaches for including energy flows into material flow simulation are merely dependent on two issues: the first one is programming and coding work if the software allows it dependent on the modeling approach chosen, the second one is the scope of the simulation model.…”
Section: State Of Researchmentioning
confidence: 99%
“…The usefulness of Discrete-Event-Simulation (DES) in manufacturing application is nowadays undisputable and has been demonstrated in various studies [3], hence diverse commercial simulators like Arena, FlexSim, Plant-Simulation, Anylogic, just to name a few, support the planning and optimization of manufacturing systems. But the implementation of energy related functions or indicators or other environmental-oriented functions within commercial simulators is not realized yet, although recent empirical studies have shown that companies see the combination of simulation enhanced by the empirical perspective as a supporting methodology [4] and requirements for future eco-oriented factories claim the same issue [5]. Approaches for including energy flows into material flow simulation are merely dependent on two issues: the first one is programming and coding work if the software allows it dependent on the modeling approach chosen, the second one is the scope of the simulation model.…”
Section: State Of Researchmentioning
confidence: 99%